The impact of global English on cultural identities in the United Arab Emirates - Hopkyns, Sarah. (New York, NY)
1 online resource.
Keywords: This book provides a nuanced portrait of the complexities of the cultural and linguistic landscape in the United Arab Emirates, unpacking the ever shifting dynamics and attitudes between and about English and Arabic in the region in today's era of superdiversity.// Employing a qualitative phenomenological approach which draws on a rich set of data from questionnaires and focus groups comprising both Emirati and expatriate students and teachers, Hopkyns problematizes the common binary East-West paradigm focused around the tension between the use of English and Arabic in the UAE. Key issues emerging from the resulting analysis include the differing attitudes toward English and in particular, English Medium Instruction, the impact of this tension on identity, and the ways in which the two languages are employed in distinct ways on an everyday scale. // The volume will be of particular interest to students and scholars interested in issues around language and identity, language policy and planning, multilingualism, translanguaging, and language and education.